PEMANFAATAN EKOENZIM KULIT KOPI DAN KULIT PEPAYA SEBAGAI SUMBER HARA BUDIDAYA SAWI MELALUI FLOATING RAFT SYSTEM HYDROPONICS - Sari, Kiky Nurfitri; Prawanto, Andika; Meilina Sari , Indriati (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
One effort that can be made to increase the quantity and quality of Chinese cabbage is by using a hydroponic cultivation system. The hydroponic cultivation system can maintain many plants in limited land conditions. However, the high economic cost of hydroponic nutrients necessitates the utilization of organic materials. One organic material that can be utilized as a nutrient source is coffee fruit peel and papaya peel. This study aims to obtain the effectiveness of utilizing coffee peel and papaya peel eco-enzymes as a nutrient source for cultivating Chinese cabbage using the floating raft system hydroponics. The experimental design that will be used in this study is a Randomized Complete Block Design (RCBD) with factorial factors, namely the type of nutrient and variety of Chinese cabbage which is repeated 3 times. The results of the study showed that the best treatment was indicated by the appearance of the application of eco-enzymes from coffee peel and papaya peel as a substitute nutrient source in hydroponics affecting various growth characteristics of Chinese cabbage plants. Both the type of fertilizer, plant variety, and the interaction between the two had a significant effect on plant height, number of leaves, leaf length, leaf width, and fresh weight of Chinese cabbage plants.